In Patients with Covid-19, The Association of Diabetes Melltus and Impaired Glucose Tolerance - Zaryab Muhammad, Muhammad Khubaib, Syed Sarmad Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Patients with COVID-19 are being studied to assess the prevalence of diabetes mellitus and decreased glucose tolerance. Study Design: Cross-sectional study Place and Duration: THQ hospital Jaranwala, Punjab medical college Faisalabad. Dec 2020-Nov 2021 Methods: In this research, one hundred and sixty individuals, both males and females, who had coronavirus illness, were included. The ages of the patients varied from 20 to 75 years. Following the receipt of informed written consent, we gathered extensive demographic information on all of the enrolled patients, including their age, gender, BMI, educational achievement, and location of residence, as well as their medications. The blood of all of the patients was tested for corona disease using the RT-PCR method. The 75-g oral glucose tolerance test was performed after screening positive participants (fasting capillary glucose >100 mg/dl and 200 mg/dl) and each sixth consecutive negative subject (fasting capillary glucose 100 mg/dl) for a total of seven consecutive days. For the purpose of data analysis, the SPSS 24.0 programme was used. Results: Patients included in the study were on average 62.8±10.35 years old, with a BMI of 30.10±17.35kg/m2. More over half of the people in the study were male 100 (62.5%), while the other were 60 (37.5%) female. Patients were illiterate in the majority of cases. Hypertension, hyperlipidemia, chronic renal disease, and coronary artery disease were the most prevalent co-morbidities. Diabetes mellitus was found in 56.3 % of the individuals studied, with the vast majority of cases being pre-existing. Impaired glucose tolerance was seen in 40% of the instances in which pancreatic cancer was the most common. Intubation was used in 37 (23.1%) studied. There were a total of 22 (13.8 %) deaths in this study. Conclusion: Covid-19 was discovered to be more common in persons with diabetes and impaired glucose metabolism. Another sign of primary infection that was previously misunderstood has been connected to an abnormality in glucose metabolism. To get to the bottom of the disease's pathogenesis, researchers need to look into how SARS-CoV-2 impacts glucose metabolism.